2019
DOI: 10.1002/ece3.5442
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen controls the net primary production of an alpine Kobresia meadow in the northern Qinghai‐Tibet Plateau

Abstract: Net primary production (NPP) is a fundamental property of natural ecosystems. Understanding the temporal variations of NPP could provide new insights into the responses of communities to environmental factors. However, few studies based on long‐term field biomass measurements have directly addressed this subject in the unique environment of the Qinghai‐Tibet plateau (QTP). We examined the interannual variations of NPP during 2008–2015 by monitoring both aboveground net primary productivity (ANPP) and belowgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…This suggests that soil nutrients which are classically considered to be variable and in this system may be most strongly controlled mechanistically by amount of rainfall, and both soil C and N which classically only change with long-term or very disruptive manipulations ecosystem change are what is driving separation in multivariate space among years. Our findings are consistent with previous studies showing N limitation in grassland ecosystems ( Bassin et al, 2007 ; Dai et al, 2019 ). Alpine grasslands are usually N-limited, therefore N deposition can release such nutrient restriction to some degree.…”
Section: Discussionsupporting
confidence: 94%
“…This suggests that soil nutrients which are classically considered to be variable and in this system may be most strongly controlled mechanistically by amount of rainfall, and both soil C and N which classically only change with long-term or very disruptive manipulations ecosystem change are what is driving separation in multivariate space among years. Our findings are consistent with previous studies showing N limitation in grassland ecosystems ( Bassin et al, 2007 ; Dai et al, 2019 ). Alpine grasslands are usually N-limited, therefore N deposition can release such nutrient restriction to some degree.…”
Section: Discussionsupporting
confidence: 94%
“…For instance, in the desert ecosystem, the plant in low precipitation condition could allocate less biomass to the leaf to avoid more moisture loss via evapotranspiration and allocate more biomass to the root to obtain more moisture and soil nutrients from a greater volume of soil (Fan et al, ; Wu et al, ). However, in the alpine ecosystem with low temperature and short growth season, the nutrient content was less as the soil nutrient supplement of the alpine ecosystems is strongly determined by nutrient mineralization (Dai, Ke, Du, Zhang, et al, ; Dai, Ke, Guo, et al, ).Therefore, there may exist trade‐off between belowground organ to capture soil nutrient and aboveground organ to capture more carbon, according to the carbon is fixed by leaves and the water or mineral nutrients were absorbed by root (McConnaughay & Coleman, ); that is, the plant might choose to obtain more biomass to plant organs that associated with the acquisition of that resource at the cost of reducing the structures biomass associated with acquisition of another resource. Moreover, this evidence was supported by the seasonal dynamics of AGB and BGB in the alpine ecosystem in a previous study (Dai, Guo, Du, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…humilis is one of the dominant species in alpine meadows of the QTP (Dai et al, 2021). Studying its morphological changes in response to grazing treatments is important for the sustainable utilization and maintenance of species diversity in the QTP alpine meadows (Guo et al, 2017;Zhang Q. et al, 2019). Our results showed that K. humilis developed adaptive strategies in response to different grazing disturbances, with significant differences observed in monocot biomass and material partitioning patterns among the different grazing treatments.…”
Section: Morphological Changes Of K Humilis In Response To Individual...mentioning
confidence: 68%
“…Thus, the S+Y treatment produced compensatory growth in K. humilis, which could have also increased the biomass. The earlier regreening also provides an advantage for K. humilis to utilize ecological niches (Zhang L. et al, 2019). This relatively reduced the competitive pressure of K. humilis with other species under S+Y treatment (Wang et al, 2014).…”
Section: Morphological Changes Of K Humilis In Response To Individual...mentioning
confidence: 99%